Configuration Analysis of Mainsteam Stop Valve-Governor Valve in a Supercritical Steam Turbine Using Computational Fluid Dynamics to Minimize Throttle Losses - Fahmi, Jauhar; S. Silviana; Sulistyo (Universitas Muhammadiyah Sidoarjo, 2025)
Quantification of losses and prediction of the technical feasibility of a proposed modified system through computational fluid dynamics (CFD) numerical analysis constitute the focus of this study. The system involves a configuration of four sets of Main Steam Stop Valves and Regulating Valves (4MSVGV), which are known to operate at low valve openings (<30%) compared to two sets of MSVGV (2MSVGV) to serve normal load demand. Using CFD modeling, the 2MSVGV configuration demonstrates the ability to serve all load ranges with a general requirement of GV lifting below 82mm. To quantify throttle losses, the principles of entropy generation and exergy destruction are employed. The modified configuration of 2MSVGV, which has a wider valve opening, consistently exhibits lower exergy destruction than the 4MSVGV configuration. Furthermore, a review of the 4MSVGV configuration reveals that GV will be the dominant contributor to exergy destruction compared to MSV. At a load of 855MW, the exergy destruction in the 4GV reaches 21MW, while it is 14MW for the modified 2GV system. The total average improvement in exergy destruction rate with the modified 2MSVGV system is about 2.05MW.